Quantitative analysis of the effect of the PAY1 gene on rice canopy structure during different reproductive stages - Cui-lan WEI; Bing-shuai CAO; Shan HUA; Bao-guo LI (Journal of Integrative Agriculture, 2022)
The leaf and stem types are core structural characteristics of the rice phenotype that determine the light interception ability of the canopy and directly affect crop yield. The PLANT ARCHITECTURE AND YIELD 1 (PAY1) gene has been shown to alter the prostrate growth habit of wild rice and to inhibit the wild rice prostrate growth gene PROSTRATE GROWTH 1 (PROG1). In this paper, the wild rice introgression line YIL55, which contains the PROG1 gene; its mutant, PAY1; and its parent, TQ, were used as test varieties to construct three-dimensional (3D) canopy structure models based on 3D digital assay technology. On this basis, quantitative analyses of the PAY1 gene and the plant leaf and stem types at the jointing, heading and filling stages were performed. Under the influence of the PAY1 gene, the plant stem and leaf angles from vertical decreased significantly; the plants were upright, with larger leaves; the culm angle changed from loose to compact; and the average tiller angle during the three key reproductive stages decreased from 44.9, 28.5 and 21.3° to 17.6, 8.4 and 10.5°, respectively. Moreover, the PAY1 mutant retained the PROG1 gene characteristic of exhibiting dynamic changes in the tiller angle throughout the growth period, and its culm angle changed from loose during the jointing stage to compact during the heading stage. The measurements of photosynthetically active radiation (PAR) in the canopy also showed that the mutant PAY1 allowed more PAR to reach the bottom of the canopy than the other varieties. The light-extinction coefficients for PAY1 at the jointing, heading and filling stages were 0.535, 0.312 and 0.586, respectively, which were lower than those of the other two varieties. In this study, the influence of the PAY1 gene on rice canopy structural characteristics was quantitatively analyzed to provide effective canopy structure parameters for breeding the ideal plant type.